Noise correlations controlled by dressed suppression and enhancement. (9th September 2016) - Lan, Huayan; Ahmed, Irfan; Wang, Hang; Yang, Yiheng; Tang, Haijun; Zhang, Yiqi; Zhang, Yanpeng
Abstract: The intensity noise correlations between anti-Stokes and Stokes fields, generated from spontaneous parametric four-wave mixing (SP-FWM) process have been investigated in a ladder-type three-level system of sodium atomic vapor. By introduction of an external dressing field, the strengthened (weakened) correlations are obtained under enhancement (suppression) condition of SP-FWM. Besides, sharp correlations have been obtained as attributed to a pair of non-classical beams generated from amplified spontaneous emission.